2008
DOI: 10.1186/1745-6215-9-58
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative oxygen fraction – effect on surgical site infection and pulmonary complications after abdominal surgery: a randomized clinical trial. Rationale and design of the PROXI-Trial

Abstract: Background: A high perioperative inspiratory oxygen fraction may reduce the risk of surgical site infections, as bacterial eradication by neutrophils depends on wound oxygen tension. Two trials have shown that a high perioperative inspiratory oxygen fraction (FiO 2 = 0.80) significantly reduced risk of surgical site infections after elective colorectal surgery, but a third trial was stopped early because the frequency of surgical site infections was more than doubled in the group receiving FiO 2 = 0.80. It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 44 publications
2
90
0
1
Order By: Relevance
“…60,61 The potential beneficial impact of reducing the risk for surgical site infection (SSI) has been suggested, but likewise, this has not been proven conclusively. [62][63][64] Research suggests that supplementing the patient with oxygen could facilitate improved healing by enhancing bacterial killing and angiogenesis, reducing surgical site infection rates, and increasing wound tensile strength. 65 The independent role of increased F I O 2 on surgical site infection in clinical practice is not entirely clear, 66 but the studies conducted with a higher oxygen fraction (F I O 2 0.8) have not shown adverse effects on pulmonary function.…”
Section: Potential Beneficial Therapeutic Effects Associated With Higmentioning
confidence: 99%
“…60,61 The potential beneficial impact of reducing the risk for surgical site infection (SSI) has been suggested, but likewise, this has not been proven conclusively. [62][63][64] Research suggests that supplementing the patient with oxygen could facilitate improved healing by enhancing bacterial killing and angiogenesis, reducing surgical site infection rates, and increasing wound tensile strength. 65 The independent role of increased F I O 2 on surgical site infection in clinical practice is not entirely clear, 66 but the studies conducted with a higher oxygen fraction (F I O 2 0.8) have not shown adverse effects on pulmonary function.…”
Section: Potential Beneficial Therapeutic Effects Associated With Higmentioning
confidence: 99%
“…The authors suggest a number of cell-level mechanisms to explain this finding; nevertheless, the results have not since been replicated. Five other randomized trials have been reported in the literature, [36][37][38][39][40] and all but one 36 have shown equivalence.…”
Section: Hyperoxiamentioning
confidence: 99%
“…Notably, in the latter report the sample size was small and there was a difference in the baseline characteristics of the groups. A prospective trial randomizing patients to either 30% or 80% supplemental oxygen during and two hours after surgery, did not find any difference in several outcome measures including death, pulmonary complications and wound healing 64 . Of note, the administration of oxygen to the aged may be limited by the finding that although arterial oxygen tension did not decrease with age, there was reduced steady-state transfer of carbon monoxide in the lungs 65 .…”
Section: Iiia Oxygen Administrationmentioning
confidence: 99%